Apple trees as a possible monitor and phytoremediator of urban and industrial areas in Chelyabinsk, Russian Federation - TATYANA G. KRUPNOVA; NATALIA L. NAUMOVA; OLGA V. RAKOVA; OLGA M. BURMISTROVA; EVGENY A. BURMISTROV (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Krupnova TG, Naumova NL, Rakova OV, Burmistrova OM, Burmistrov EA. 2021. Apple trees as a possible monitor and phytoremediator of urban and industrial areas in Chelyabinsk, Russian Federation. Biodiversitas 22: 2824-2828. Apple trees are cultivated worldwide and are the most widely grown fruit crops in the South Ural region. This study examines the suitability of apple trees for biomonitoring and phytoremediation. We collected the leaves and fruits of the apple (Malus domestica Borkh.) trees and the surrounding soil from three areas in Chelyabinsk, a typical Russian industrial city. The leaves, fruits and soils were analyzed for metal(loid) content (As, B, Cd, Co, Cr, Cu, Fe, Ga, In, Hg, Mn, Ni, Pb, Se, Sn, Sr, and Zn). The results were obtained using mass spectrometry with inductively coupled plasma (ICP-MS). We found a response in the apple tree defense system to the action of heavy metals in the synthesis of biologically active substances. The data gave information about the environmental state of soils collected in the zones of influence of metallurgical industrial enterprises. However, the trees did not assimilate or tolerate high concentrations of metal(loid)s in the leaves and they cannot be recommended for phytoremediation.